IMPLEMENTASI BIMBINGAN KONSELING ISLAM DALAM MENANGANI MASALAH KENAKALAN SISWA DI SMAN 1 TANTA - Nurhayati Nurhayati (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Student delinquency in schools is a problem that affects the learning environment and students' character development. Islamic Counseling Guidance serves as a solution to address deviant behavior through an approach based on Islamic values. This study aims to analyze the implementation of Islamic Counseling Guidance in handling student delinquency at SMAN 1 Tanta and to identify its effectiveness in shaping better student character. This research employs a qualitative approach with a case study method. Data were collected through observations, interviews with counseling teachers and students, and documentation of counseling activities. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of Islamic Counseling Guidance is carried out through Islamic character development, an individualized counseling approach, religious activities, and collaboration with parents and teachers. The positive impacts of this program include a decrease in disciplinary violations, increased students' spiritual awareness, and improved relationships between students and teachers. However, challenges such as low student awareness and environmental influences remain obstacles in its implementation. In conclusion, Islamic Counseling Guidance is effective in addressing student delinquency at SMAN 1 Tanta through a more persuasive and religious approach. Innovative strategies and support from various stakeholders are needed to enhance the success of this program.